INVESTIGATION OF AUTISTIC INDIVIDUALS’ CHARACTERISTICS AND THEIR PARENTS' BROAD AUTISM PHENOTYPE AND ALEXITHYMIA CHARACTERISTICS - Aydan AYDIN (Fırat University, 2019)
Getting families’ support and cooperating with them have great importance while planning education services offered to children with autism. For this reason it would be useful to know parents’ characteristics to improve functionality of the services which will be offered to them and their children with autism. The aim of this research is to investigate the relationship between autistic children parents’ broad autism phenotype and alexithymia characteristics and autistic in